Total Bakteri, Angka TBA, Dan Sifat Sensoris Bumbu Dasar Putih Pasta Berdasarkan Lama Simpan - Dewa Febrian Riyandi; Yunan Kholifatuddin Sya'di; Nurhidajah Nurhidajah (Universitas Muhammadiyah Semarang, 2022)
Seasoning is a spice ingredient that is processed into dishes that have a high level of aroma and taste without losing the components of natural ingredients. The characteristics of the seasoning are yellowish white, distinctive aroma and wet texture. Seasoning damage can occur due to oxidation of fat which is influenced by humidity at room temperature. The purpose of this study was to determine the relationship between shelf life and total bacteria, TBA number, and sensory properties of the experimental type of white pasta seasoning. For making white paste seasoning, all ingredients are selected fresh and weighed, then the blanching process is carried out by soaking all ingredients in hot water at 80oC for 5 minutes. Then blend all ingredients using oil and sauté over low heat for about 30 minutes. This study used a monofactor completely randomized design, with 5 treatments of shelf life (0, 5, 10, 15, and 20 days) and 5 replications. The results of this study showed an increase in bacterial growth during 20 days of storage. At storage 0, 5, 10, and 15 days the results were not significantly different, while at storage 20 days gave significantly different results in the long storage treatment. All the old treatments for storing white pasta base spices were acceptable to the panelists.